Exploring gellan gum-based hydrogels for regenerating human embryonic stem cells in age-related macular degeneration therapy: A literature review - Mthabisi Talent George Moyo; Terin Adali; Pinar Tulay (Regenerative Therapy)
Age-related macular degeneration (AMD) is a progressive ocular disease marked by the deterioration of retinal photoreceptor cells, leading to central vision decline, predominantly affecting the elderly population worldwide. Current treatment modalities, such as anti-VEGF agents, laser therapy, and photodynamic therapy, aim to manage the condition, with emerging strategies like stem cell replacement therapy showing promise. However, challenges like immune rejection and cell survival hinder the efficacy of stem cell interventions. Regenerative medicine faces obstacles in maximizing stem cell potential due to limitations in mimicking the dynamic cues of the extracellular matrix (ECM) crucial for guiding stem cell behaviour. Innovative biomaterials like gellan gum hydrogels offer tailored microenvironments conducive to enhancing stem cell culture efficacy and tissue regeneration. Gellan gum-based hydrogels, renowned for biocompatibility and customizable mechanical properties, provide crucial support for cell viability, differentiation, and controlled release of therapeutic factors, making them an ideal platform for culturing human embryonic stem cells (hESCs). These hydrogels mimic native tissue mechanics, promoting optimal hESC differentiation while minimizing immune responses and facilitating localized delivery. This review explores the potential of Gellan Gum-Based Hydrogels in regenerative AMD therapy, emphasizing their role in enhancing hESC regeneration and addressing current status, treatment limitations, and future directions.